Perkembangan dan Pola pertumbuhan Sektor Pertanian dalam Pembangunan Ekonomi - Syahrial Syahrial; Ilham Martadona; Nurkholiza Harahap (Hasanuddin University, 2023)
The agricultural sector is one sector that has opportunities in economic development activities. This study aims to 1) Analyze the economic development of the agricultural sector in Solok Regency. 2) Analyzing the structure of economic growth in the agricultural sector in Solok Regency. The basic method used is the Entropy Diversity Index and Klassen Typological Analysis. The results of the analysis show that three sub-sectors in the agricultural sector in Solok Regency are still underdeveloped. The economic growth of the agricultural sector in Solok Regency, which of 61 commodities including the food, horticulture, and plantation sub-sectors is the most widely occupied, behind at 39 percent, prime at 23 percent, developing at 20 percent, and potential at 18 percent. The government must be able to make policies to increase production, prioritize advanced and fast-growing commodities, and improve underdeveloped commodities by conducting counseling and improving agricultural technology so as to improve the economy in Solok Regency.